The Catholic Church in mainland China: A look back over 40 years - Myers, James T. (Issues & studies, 1988)
After briefly reviewing the history of the Catholic Church in mainland China, the paper traces the attitudes of the Chinese communists to the Catholic Church. New period to "religious freedom" in China under Deng Xiaoping. The Vatican's interests in some sort of dialogue with the PRC. (DÜI-Sen)